Artists Choose Artists : Philadelphia Art Now - Courtney, Julie; Kaplan, Janet A.; Tannenbaum, Judith E. ([Philadelphia] : Institute of Contemporary Art, University of Pennsylvania, 1991)
Adams, Phoebe ; Anderson, Harry ; Andrade, Edna ; Angle, Warren O. ; Asman, Robert ; Bachman, S.A. ; Baguskas, Eugene ; Bergner, Lanny ; Bourassa, Anne ; Burko, Diane ; Carnell, Jack ; Chimes, Thomas ; etc.
Artists Choose Artists : Philadelphia Art Now, Institute of Contemporary Art, University of Pennsylvania, Philadelphia, January 19 - March 3, 1991
boek
Keywords: Philadelphia